1997
DOI: 10.1212/wnl.49.5.1210
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the dose of zolmitriptan (Zomig,* 311C90) for the acute treatment of migraine

Abstract: This study investigated the efficacy of zolmitriptan (Zomig, formerly 311C90) in acute migraine therapy. Patients with a history of migraine were randomized in a double-blind, multicenter, placebo-controlled, dose range-finding study of oral zolmitriptan 1, 2.5, 5, or 10 mg versus placebo for the treatment of a severe or moderate migraine headache. Patients with persistent or recurrent headache 4 to 24 hours after the initial dose, who did not take escape medication, were eligible to receive a second blinded d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
81
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(88 citation statements)
references
References 8 publications
5
81
2
Order By: Relevance
“…Finally, the mean 24 hour headache recurrence rate is 30% for the 2.5 mg tablet and 31% for and the zolmitriptan 5 mg tablet as compared to 38% and 48% for the placebo, Figure 3 and 4. 43,[63][64][65] There is also evidence of a consistent response across multiple attacks in individual patients for both, the 2.5 mg and 5 mg tablets of zolmitriptan. Tuchman et al showed that the 2-hour headache response across attacks was 85% for the 2.5 mg tablet and 79% for the 5 mg zolmitriptan tablet.…”
Section: Clinical Effi Cacy Effi Cacy In Migrainementioning
confidence: 92%
See 1 more Smart Citation
“…Finally, the mean 24 hour headache recurrence rate is 30% for the 2.5 mg tablet and 31% for and the zolmitriptan 5 mg tablet as compared to 38% and 48% for the placebo, Figure 3 and 4. 43,[63][64][65] There is also evidence of a consistent response across multiple attacks in individual patients for both, the 2.5 mg and 5 mg tablets of zolmitriptan. Tuchman et al showed that the 2-hour headache response across attacks was 85% for the 2.5 mg tablet and 79% for the 5 mg zolmitriptan tablet.…”
Section: Clinical Effi Cacy Effi Cacy In Migrainementioning
confidence: 92%
“…The effi cacy of zolmitriptan tablets has been demonstrated in multiple double-blind placebo controlled trials. 43,[63][64][65] At 2 hours, the mean headache response (HR) rate is approximately 64% for the 2.5 mg zolmitriptan tablet as compared to 35% for placebo; similarly the 2 hr HR rate is 65% for the zolmitriptan 5 mg tablets as compared to 27% for placebo. In addition the mean 2 hour pain free (PF) rate was 24.5% for the 2.5 mg zolmitriptan tablet and 28.6% for the 5 mg tablet, as compared to the placebo 2 hr PF rates of 8.5% and 4.3% respectively.…”
Section: Clinical Effi Cacy Effi Cacy In Migrainementioning
confidence: 99%
“…Improved response to triptan medications may occur through several methods. One of these would be to increase the dose of the oral triptan [8,9]. Another approach would be to use a SC route of administration of the drug as is available for sumatriptan.…”
Section: Introductionmentioning
confidence: 99%
“…However parenteral administration of the non-selective 5-HT1 agonist dihydroergotamine (DHE) was significantly more effective than placebo for this condition [11]. Sumatriptan [12], zolmitriptan [13], rizatriptan [14] and naratriptan [15] have also been shown effective for aborting attacks of menstrual migraine, and also for relieving the associated nausea and vomiting.…”
Section: Acute Treatment Of Menstrual Migrainementioning
confidence: 99%